2021
DOI: 10.1111/jce.15199
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint pacing for cardiac resynchronisation therapy in patients with heart failure: A systematic review and meta‐analysis

Abstract: Introduction Multipoint pacing (MPP) has been proposed as an effective way to improve cardiac resynchronisation therapy (CRT) response. We performed a systematic review and meta‐analysis evaluating the efficacy of CRT delivered via MPP compared to conventional CRT. Methods A literature search was performed from inception to January 2021 for studies in Medline, Embase and Cochrane databases, comparing MPP to conventional CRT with a minimum of 6 months follow‐up. Randomised and nonrandomised studies were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Advancements in CRT have led to the exploration of alternative pacing sites, the development of newer device-based algorithms, and strategies when traditional CRT is not feasible or effective. Strategies targeting "multi-points" have shown superiority over classic CRT [2]. Additionally, conduction system pacing has arisen as a promising technique [3].…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in CRT have led to the exploration of alternative pacing sites, the development of newer device-based algorithms, and strategies when traditional CRT is not feasible or effective. Strategies targeting "multi-points" have shown superiority over classic CRT [2]. Additionally, conduction system pacing has arisen as a promising technique [3].…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that there may be a delayed response to biventricular pacing beyond the initial 6 months owing to a myocardial substrate that needs more time to fully undergo reverse remodelling, or heart failure medication that continues to be up titrated-whether that be with MPP, MSP, or conventional CRT. A recently published meta-analysis by Mehta et al reported that in randomised studies, there is no difference between MPP and conventional CRT ( Mehta et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While early studies of multi-point pacing demonstrated promising improvements in short-term haemodynamic and dyssynchrony outcomes, 3–5 a recent meta-analysis of multi-point pacing found no significant benefit over conventional CRT when only randomized studies were included. 6 …”
Section: Introductionmentioning
confidence: 99%